CCAFS Rwanda Deep Dive Assessment of Climate-Smart Agriculture (CSA) in the USAID Feed the Future Portfolio in Rwanda - Henry, Kevin; Ngugi, Moffatt; Quinney, Marie; Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
As part of a global effort that will inform how Feed the Future tracks CSA across the 19 focus countries (plus aligned) the CCAFS and USAID/BFS team selected five to carry out a deeper analysis of their portfolio. A visit in June 2015 by CCAFS to the Rwanda Mission highlighted the importance of addressing the effects of climate change in the agricultural sector and the current and potential benefits of CSA in Feed the Future. The five-day visit included a number of meetings with USAID Mission staff, Feed the Future implementing partners, Government of Rwanda partners, and other stakeholders, as well as a field trip to one Feed the Future project in the Southern Region. The process also included a review of documentation on the five current projects in the Feed the Future portfolio, shared in advance of the visit by USAID Rwanda staff. This report outlines the key findings of the visit and highlights some ways in which CSA can be further incorporated into the Mission’s future programming